Islam, globalization and public sector governance - Quddus, S. M. Abdul (International Islamic University Malaysia, 2019)
Globalization started sometime ago and is an ongoing process. It is a diverse phenomenon, which has had tremendous impact on all aspects of human life (Larry Ray, 2007). The spread of the culture of globalization can predominantly be attributed to the usage of modern electronic media such as the internet. As Islam is a global phenomenon, it becomes apparent that its principles should be held in the esteem befitting its status and not disregarded as irrelevant. Religious people of all age categories must deign to adapt their traditions to deal with the challenged of modernity. The end goal of globalization is thus to assess and integrate common ground into the world views of Islamic versus Western values rather than provoke bi-polarization and discord. As globalization in its current iteration predominantly stems from the influences of the West, it is paramount to scrutinize the differences in the Muslim interpretation of globalization in relation to its modern incarnation, to explore its differing definitions, the fluctuating goals of the educational systems, the sidelining of local traditions and languages, factors derived from the advent of “brain-drain” from certain nations, appropriate Muslim actions in response to globalization, and finally onto the question, how public sector management should be reformed in line with the reality of globalization and Islamic philosophy of government and administration in the contemporary era? However, following the example of the Western capitalist models and excluding religious public sector reform has produced varied reactions in MMCs. Such reactions include widespread social alienation and accelerated unhappiness and promotion of restless competition rather than cooperation. All these realities raise some unavoidable questions and debates that need to be properly addressed both from theoretical and practical perspectives. A refocused attention at the philosophy of public sector governance in light of the role of religion on the globalized and technology-driven world is an important endeavor to undertake. Thus the main objective of this paper is to explore an administrative model for public sector governance that will fulfil the socio-economic, technological and spiritual needs of a society. Data for this paper will be collected mainly from secondary sources i.e. content analysis. ‘Islamic administrative model’ as suggested by Al-Buraey will be used as the theoretical underpinning for this study.